A study on the user perception of the safety aspect at the extreme park / Nor Farah Aida Mohamed Zeble - Mohamed Zeble, Nor Farah Aida (Faculty Architecture, Planninng and Surveying, 2015)
The individual perception will always change and depends on the individual opinion, Through users' perception as well, the quality and activities of some places can improve. Extreme Park offers a group of extreme game such as wall climbing, skateboarding, bicycle motocross, paintball, Parkour and mountain biking. This extreme game attracts large number of people, especially teenagers. People nowadays are exposed to the extreme game. Those games not only offered enjoyment to the users, but at the same time offering user's risk of accident. This study aims to investigate the user’s perception on the safety aspect apply in the extreme park and also the way to improve the safety aspect of the extreme park. In order to achieve a good safety aspect of the extreme park. Result that obtained from the data analysis shows that most of the users of Extreme Park understand the safety meaning. When users understand the purpose of safety at the extreme park they likely to become more aware of any activity undertaken at the extreme park. The end of this research will give results about safety aspect approach at the Extreme Park and way to improve safety aspect at the extreme park